EXPOSURE TO HOUSEHOLD AIR POLLUTION FROM BIOMASS COOKSTOVES AND BLOOD PRESSURE AMONG WOMEN IN RURAL HONDURAS: A CROSS-SECTIONAL STUDY - Young, Bonnie N. (Indoor Air, 2018)
Growing evidence links household air pollution exposure from biomass cookstoves with elevated blood pressure. We assessed cross-sectional associations of 24-hour mean concentrations of personal and kitchen fine particulate matter (PM(2.5)), black carbon (BC), and stove type with blood pressure, adjusting for confounders, among 147 women using traditional or cleaner-burning Justa stoves in Honduras. We investigated effect modification by age and body mass index. Traditional stove users had mean (standard deviation) personal and kitchen 24-hour PM(2.5) concentrations of 126 μg/m(3) (77) and 360 μg/m(3) (374), while Justa stove users’ exposures were 66 μg/m(3) (38) and 137 μg/m(3) (194), respectively. BC concentrations were similarly lower among Justa stove users. Adjusted mean systolic blood pressure was 2.5 mmHg higher (95% CI, 0.7 to 4.3) per unit increase in natural log transformed kitchen PM(2.5) concentration; results were stronger among women 40 years or older (5.2 mmHg increase, 95% CI, 2.3 to 8.1). Adjusted odds of borderline high and high blood pressure (categorized) were also elevated (odds ratio=1.5, 95% CI, 1.0 to 2.3). Some results included null values and are suggestive. Results suggest that reduced household air pollution, even when concentrations exceed air quality guidelines, may help lower cardiovascular disease risk, particularly among older subgroups.